Visual fields after anti-vascular endothelial growth factor therapy for retinopathy of prematurity - Kazuki Imai; Shumpei Obata; Riko Matsumoto; Ayaka Nishida; Maki Iwasa; Masashi Kakinoki; Osamu Sawada; Yoshitsugu Saishin; Masahito Ohji (PLoS ONE, 2025)
It is known that laser photocoagulation for retinopathy of prematurity (ROP) can cause visual field defects. There are no reports comparing the visual fields of ROP patients treated with anti-vascular endothelial growth factor (anti-VEGF) therapy and those of normal controls. A retrospective cohort study was conducted for the anti-VEGF therapy group and a prospective study was carried out for the normal control group. Visual fields were tested using Goldmann perimetry. The viewing angles in eight directions (upper, nasal-upper, nasal, nasal-lower, lower, temporal-lower, temporal and temporal-upper) and the total angle were compared between the two groups. Children aged 4 years and older who could undergo a visual field test were included. The anti-VEGF therapy group comprised children treated for Type 1 ROP with intravitreal injections of bevacizumab or ranibizumab between April 2010 and September 2019. The normal control group comprised children with best-corrected visual acuity of 1.0 or better, and without a history of any ophthalmologic diseases that cause visual field defects. Thirteen eyes of 7 patients in the anti-VEGF therapy group and 10 eyes of 5 patients in the normal control group met the criteria. The visual field angles were significantly narrower in the anti-VEGF therapy group, compared with the normal control group, for the total, and the upper, nasal-upper, nasal-lower, lower, temporal-lower, temporal and temporal-upper directions (502 versus 540 degrees, P = 0.002; 53 versus 57 degrees, P = 0.02; 55 versus 62 degrees, P = 0.04; 56 versus 61 degrees, P = 0.005; 60 versus 66 degrees, P = 0.005; 72 versus 77 degrees, P = 0.04; 82 versus 90 degrees, P = 0.005; and 62 versus 72 degrees, P = 0.002, respectively). Patients with ROP may exhibit narrower-than-normal visual fields after anti-VEGF therapy.